The Influence of Human Resources Competency Management on the Business Success of Small and Medium Enterprises - Klepić, Iva (Naše gospodarstvo/Our economy, 2022)
The success of the organization is based on the quality of human resources, their competencies, motivation, loyalty, and their business results. The basic aim of this research is to determine whether and to what extent human resources competency management influences the business success of small and medium enterprises (SMEs). The empirical research was conducted in 234 SMEs in the Federation of Bosnia and Herzegovina in January 2021. An original questionnaire was created for the survey, which gathered the opinions of top managers. In the paper, human resources competency management is viewed as a process consisting of: determining the required competencies, determining current competencies and the competency gap and undertaking activities to ensure and develop the necessary competencies. For the business success of SMEs, business performance was researched through four perspectives of the Balanced Scorecard (financial, customer, internal business processes and learning and growth perspective). The research results showed the correlation between the studied variables and the influence of human resources competency management on the business success of SMEs viewed from all four perspectives. The paper includes a comparison with similar research, limitations and recommendations for future research. The originality of this work lies in creating an original model of the connection between human resources competency management and business success (performance) of SMEs as viewed through four perspectives of the BSC, which has been empirically tested. Also, no such research has been conducted in B&H to investigate the influence between the human resources competency management and the business success of SMEs